Rites of passage in a comparative perspective - Schilderman, Hans (Jaarboek voor liturgieonderzoek, 2005)
The first section outlines an accepted approach to empirical liturgical research in theology. The next three sections give a conceptual commentary on three aspects of rites of passage: their goal, form and significance. The article concludes with a section on the need for, and possibilities of, comparative empirical research into rites of passage.